EXTRAJUDICIAL KILLING OLEH APARAT PENEGAK HUKUM SEBAGAI PELANGGARAN PRINSIP DUE PROCESS OF LAW DALAM PERSPEKTIF HAK ASASI MANUSIA - Anan, Moh. Shofi; Sambas, Nandang (Collegium Studiosum Journal, 2025)
Extrajudicial killings committed by police officers in Indonesia in the context of the principle of due process of law and protection of human rights (HAM). The rule of law guarantees that every law enforcement action must be carried out fairly, transparently, and in accordance with legal procedures, but in reality, acts of extrajudicial killings still often occur. Cases of shootings by police officers, such as the shooting of students in Semarang and various other incidents in several regions, indicate serious violations of the principles of law and human rights. This study uses a qualitative normative approach by examining relevant national and international legal provisions, including Law Number 39 of 1999 concerning Human Rights, the Criminal Code, the Criminal Procedure Code, and the Regulation of the Chief of Police on the use of force in police actions. Data were obtained from laws and regulations, human rights institution documents, and related scientific literature. (1) The results of the study indicate that acts of extrajudicial killings constitute a serious violation of the principle of due process of law, reflect abuse of authority and damage the credibility of law enforcement officers. (2) This violation also has a serious impact on the protection of human rights in Indonesia, especially the right to life which is non-derogable. The legal accountability mechanism for this practice is still weak, so it is necessary to reform the monitoring system and increase the accountability of law enforcement officers.